Key Patient Experience Drivers That Result in Exemplary Overall Provider Performance Ratings in the Ambulatory Environment: A Quantitative Study. Issue 3 (July 2022) - Jurdi, Zahi R.; Crosby, Joseph F.
Abstract : This study highlights the key drivers that form particular patient impressions resulting in exemplary overall provider performance ratings across service lines in the ambulatory environment. Two national samples of CG-CAHPS data were analyzed. Results indicate variance of impact among all CG-CAHPS questions on "top-box" scores for overall rating of provider among specialties. Interestingly, the same 5 explanatory variables—provider listened carefully, provider spent enough time, provider showed respect, provider knew important information about medical history, and provider explained things clearly—had the greatest explanatory power across the primary and specialty care samples when analyzed via multiple logistic regression analysis.